ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PADA LAYANAN VIDEO ON DEMAND (Studi Pada Pengguna Netflix) - Azalia, Davita Wemona; Magnadi, Rizal Hari (Faculty of Economics and Business Diponegoro University, 2020)
The present study is to identified factors that affecting consumer purchase decision of Video On Demand which is Netflix. The conceptual framework for this study included two variable of actual usage technology as proposed by TAM which are Perceived Ease of Use and Perceived Usefulness. Furthermore, Perceived Price and Social Influence was added to the framework. Sample Data is done by interview, while the questionnaire used as the tools in data collection. Research sample are 100 respondents who are aware of Netflix and already used Netflix This research uses multiple linear regression analysis techniques that are processed using SPSS. The results of this research found that Perceived Ease of Use, Perceived Usefulness, Perceived Price and Social Influence have a positive and significant influence on Purchase Decision.